Designing and Analysis of IEEE 802.11 MAC for UAVs Ad Hoc Networks - Shah, A. F. M. Shahen; Ilhan, Haci; Tureli, Ufuk (IEEE, 2019)
Unmanned aerial vehicles (UAVs) are popular because they are low cost and do not put in danger human pilot lives. In this study, performance of IEEE 802.11 medium access control (MAC) for UAVs ad hoc networks is studied using an analytical model based on Markov chain model. Three dimensional (3D) nature and high mobility are main characteristics of UAVs ad hoc networks which are considered. The relationship among parameters and performance metrics such as throughput, packet dropping rate (PDR), and delay expressions are derived. Complexity analysis and numerical results are presented. Moreover, to ensure safe and efficient communication in UAVs ad hoc networks, IEEE 802.11 MAC can satisfy the performance requirements or not is investigated.
Keywords: Complexity; IEEE 802.11; MAC; Markov chain model; Mobility; Performance; UAVs; Computer Science; Engineering; Telecommunications